Some aspects of southwest monsoon as seen In satellite cloud imagery (MAUSAM, 1991)
Satellite cloud imagery for the years 1978-79 and 1984-88 have been studied. Some aspects of southwest monsoon have been documented. It has been shown that, the cross-equatorial flow, its location and intensity, play an important role in the onset of southwest monsoon and its activity during the season. The southern hemispheric equatorial trough plays the role of regulating the cross-equatorial flow and thus leads to the development of different phases of southwest monsoon. The inverse relationship between the intensity of southern hemispheric equatorial trough and the monsoon activity can be used as a tool in foreshadowing dry and wet spells. The results presented in the paper are helpful in understanding the physical processes taking place in the  monsoonal  atmosphere.